Effect of sowing dates and nutrient management practices on important parameters in Toria (Brassica rapa L. var. Toria) - Tiryak Kumar Samant; Debabrata Panigrahi (Journal of Oilseed Brassica, 2026)
Effect of sowing date and nutrient management practices on growth, yield, nutrient uptake and economics of irrigatedToria were studied in an experiment comprised of three main plot treatments of different sowing dates viz., 15th October,30th October, 14th November and four subplots viz., RDF, RDF+Sulphur, 75% RDF+FYM, 75% RDF+FYM + Sulphur insplit plot design replicated thrice. The results revealed that sowing of Toria on 15th October recorded significantlyhigher plant height (150.1 cm), no of primary branches plant-1 (5.2), dry matter accumulation plant-1 (28.6 g), no of siliquaeplant-1 (185.1), grain yield (1524.7 kg ha-1), harvest index (25.2 %) , B:C ratio (2.4), economic efficiency (Rs.376.8 ha-1 day-1) with maximum uptake of N, P, K and S by seed. Among the nutrient management practices, application of 75%RDF+FYM + Sulphur (40kg ha-1) recorded maximum plant height (157.2 cm), dry matter accumulation plant-1 (31.0g), noof siliquae plant-1 (201.2), no of seeds siliqua-1 (12.5), grain yield (1488.3 kg ha-1) with harvest index (24.0 %). Maximum B:Cratio (2.5) and economic efficiency (Rs.358.7 ha-1 day-1) was obtained in sole application of RDF and 75% RDF+FYM 5t ha-1 respectively. Thus, sowing on 15th October and 75% RDF+FYM + Sulphur (40kg ha-1) can be practiced formaximizing yield, income, improvement of growth, nutrient uptake of irrigated Toria.